Do efficacy and effectiveness samples differ in antidepressant treatment outcome?: an analysis of eligibility criteria in randomized controlled trials - Seemüller, Florian; Möller, Hans-Jürgen; Obermeier, Michael; Adli, Mazda; Bauer, Michael; Kronmüller, Klaus-Thomas; Holsboer, Florian; Brieger, Peter; Laux, Gerd; Bender, Wolfram; Heuser, Isabella; Zeiler, Joachim; et al. (The journal of clinical psychiatry, 2010)
Article Abstract Background: Because of strict inclusion and exclusion criteria, results drawn from placebo-controlled randomized antidepressant efficacy trials may not be transferable to real-world patients. Method: This study was performed from March 2000 to September 2005 as a prospective, multicenter follow-up. Patients were recruited from February 2000 to June 2005. All patients were hospitalized (N = 1,014) and met DSM-IV criteria for major depressive episode. Assessments with the 21-item Hamilton Depression Rating Scale were conducted biweekly until discharge. According to the most commonly applied exclusion criteria in randomized controlled antidepressant efficacy trials, patients were retrospectively divided into 2 groups: (1) patients not fulfilling exclusion criteria and therefore eligible for a randomized placebo-controlled trial, referred to as "efficacy sample," and (2) patients fulfilling at least 1 exclusion criterion, not being eligible for inclusion in an efficacy trial ("nonefficacy sample"). The efficacy sample was compared with the nonefficacy sample in terms of sociodemographic and clinical baseline variables and outcome measures, such as remission and response rates, 17-item Hamilton Depression Rating Scale mean scores, time to remission, and time to response. Results: Significant differences were found, with the efficacy sample being older (P = .03) and being more often treated at a university hospital (P = .02). The efficacy sample demonstrated superior outcome only in significantly higher mean Global Assessment of Functioning scores at discharge (P = .03). There were no differences regarding remission (P = .68) and response (P = .06) rates, length of hospital stay (P = .49), 17-item Hamilton Depression Rating Scale total score at discharge (P = .13), or time to response (P = .39) or remission (P = .16). Conclusions: Both groups differed significantly in several baseline measures and final Global Assessment of Functioning scores but not in any other outcome measure. Challenging current beliefs, our findings show that results from efficacy antidepressant trials might be more generalizable than previously thought. J Clin Psychiatry Submitted: February 20, 2009; accepted June 15, 2009. Online ahead of print: August 10, 2010 (doi:10.4088/JCP.09m05166blu). Corresponding author: Florian Seemüller, MD, Department of Psychiatry, Ludwig-Maximilians-Universität, Nussbaumstrasse 7, 80336 Munich, Germany (florian.seemuellermed.uni-muenchen.de).